Portable Life Support System: Current Status and Future Perspectives - Jiang, Jingang; Chen, Yihao; Ma, Xuefeng; Zhang, Yongde; Huang, Zhiyuan; Liang, Dexian (Recent Patents on Engineering, 2020)
Background: Portable life support system is used in the battlefield, disaster and in other special circumstances such as in space exploration, and underground survey to give the wounded a life support. The most dangerous period for the injured is the first hour after an injury, which is a crucial time for treatment. If the patient's vital signs were stabilized, more than 40% of the injured could be saved. The staff can efficiently complete the task if they get effective and stable vital signs during the operation. Therefore, in order to reduce the risk of disaster and battlefield mortality to improve operational safety and efficiency, it is necessary to study the portable life support system. Objective: The study aimed to provide an overview of recent portable life support system and its characteristics and design. Methods: This paper introduces the patents and products related to a portable life support system, and its characteristics and application. Results: This paper summarizes five kinds of portable life support systems which are box type, stretcher type, bed type, backpack type and mobile type. Moreover, the characteristics of different portable life support systems are analyzed. The paper expounds the problems of different types of portable life support systems and puts forward improvement methods to solve the problems. Finally, the paper points out the future development of the system. Conclusion: Portable life support system plays an increasingly important role in health care. In terms of the structure, function and control, further development and improvements are needed, along with the research on portable life support system.
Keywords: mobile